VOIP Transmission Quality Increase using Adaptive Play-Out Buffer - Repcik, Marek (Communications - Scientific Letters of the University of Zilina, 2003)
In this paper we consider some quality aspects of VoIP (Voice over Internet Protocol) transmission. We try to increase the voice transmission quality using the adaptive play-out buffer instead of common buffer at the receiver's side. The hypothesis is that the less packet-loss probability increases the transmission quality more that the additional jitter decreases it. The aim of this paper is to formulate the problem.
Keywords: no keywords